β-Glucan: Mode of Action and Its Uses in Fish Immunomodulation - Hadiuzzaman, Md; Moniruzzaman, Mohammad; Shahjahan, Md; Bai, Sungchul C.; Min, Taesun; Hossain, Zakir (Frontiers in Marine Science, 2022)
Beta-glucan is considered as an effective immunostimulant for its binding capacity to different receptors on leukocytes leading to the stimulation in immune responses which includes bactericidal activity, cytokine productivity, and survival fit ability at cellular levels. In response to immune cell surface receptors beta-glucan stimulates to release cytokines and chemokines. It was found that these signaling proteins eventually stimulate the immunocompetent cells in fish such as monocytes, macrophages and neutrophils for killing pathogens by phagocytosis, oxidative burst and cytotoxic killing activities. They also procreate immunological memories and specific antibodies through activation of T and B lymphocytes. Researchers have proved that beta-glucan could modulate some important biochemical (serum hemoglobin, serum protein, total hemocyte count) and immunological (lysozyme activity, phagocytic activity, oxidative burst activity, phenoloxidase activity) properties providing more competent immune profile for treating fish and aquatic organisms. Beta-glucan supplemented fish showed limited sensitivity of genes involved in acute inflammatory reactions. Findings have shown that beta-glucan exerts positive impact on fish and aquatic organisms’ immunity enhancing their disease resistances by increasing functional and decreasing deleterious responses. This review focus on the basic bump of beta-glucan on fish and shellfish immunity and recent information on the use of beta-glucan in progressive aquaculture.